The Impact of Brand Image and Service Quality on Customer Loyalty, with Customer Satisfaction as A Mediator - Supriyanto, Bambang; Dahlan, Kandi Sofia Senastri (Ridwan Institute, 2024)
The study conducted at PT Kennametal Indonesia, a cutting tool industry company under the Kennametal brand, aimed to assess the impact of brand image and service quality on customer loyalty, specifically focusing on customer satisfaction as a potential mediator. Employing an empirical study approach, data were gathered via a questionnaire distributed to randomly selected customers. This resulted in 111 sets of received data, with 106 deemed suitable for analysis out of the 200 distributed questionnaires. SMART PLS 3.0 was utilized to explore the relationships between independent variables (brand image and service quality) and the dependent variable (customer loyalty) while evaluating the mediating role of customer satisfaction. The findings revealed that the service quality of PT Kennametal Indonesia did not significantly impact customer loyalty towards cutting tools, and a similar lack of significant influence was observed for brand image. It is crucial to emphasize that the term